Andrea Carosso, Cold War Narratives: American Culture in the 1950s (Altre Modernità, 2013)
Andrea Carosso, Cold War Narratives:American Culture in the 1950s(Bern, Peter Lang, 2012, 220 pp., ISBN 978-3-0343-1270-7)